Olfactory Function is Affected in Patients with Cirrhosis Depending on the Severity of Hepatic Encephalopathy - Heiser, Clemens; Haller, Bernhard; Sohn, Maximilian; Hofauer, Benedikt; Knopf, Andreas; Muehling, Tobias; Freiherr, Jessica; Bender, Martin; Tiller, Maximilian; Schmidt, Anna; Schepp, Wolfgang; Gundling, Felix (Annals of Hepatology, 2018)
Introduction and aim. Olfactory functions are altered to a variable degree by chronic liver disease. Few studies including only small populations of patients emphasized the possibility of hepatic encephalopathy (HE) influencing olfactory nervous tasks. So far, no study has explicitly focused on olfactory function depending on the severity of HE as assessed by objective diagnostic procedures. Thus we performed a study using the "Sniffin' Sticks" test system, critical flicker-fusion frequency (CFF) and clinical West Haven criteria. Material and methods. 54 cirrhotic patients with liver cirrhosis were included. Furthermore, 43 adult volunteers participating as a non-cirrhotic control group. Olfactory testing was performed using the "Sniffin' Stick" test battery (Burghart Medizintechnik, Wedel, Germany) which renders a widely-used tool both in clinical and research settings for the assessment of olfactory threshold, odor identification and discrimination. Several complications of cirrhosis were diagnosed by reference methods. Statistical analysis of cirrhosis-associated complications and their relation to olfactory function was performed. Assessment of HE and classification of different stages were performed according to clinical criteria (West-Haven criteria) and according to CFF, which was determined using a portable analyzer. Results. Olfactory function was significantly reduced in cirrhotic patients (in 61.1%) compared to controls (p < 0.001). Among cirrhotics patients, the prevalence of olfactory deficits (hyposmia, anosmia) increased with the severity of HE as assessed by CFF and clinical criteria (p = 0.008 and p = 0.097, respectively). No correlation was observed between olfactory deficits and severity of liver disease as assessed by Child-Pugh-Score, etiology of cirrhosis and complications of cirrhosis such as ascites and portal venous hypertension. Conclusions. Olfactory testing serves as a screening tool for HE and may faciliate grading of HE-severity.
Keywords: Hepatic encephalopathy; Chemosensation; Critical flicker frequency; Smell disorders